Testing the state of human erythrocytes after combined action of posthypertonic shock and amphiphilic compounds - Chabanenko, O.O.; Orlova, N.V.; Shpakova, N.M. (Reports of the National Academy of Sciences of Ukraine, 2021)
The effect of the temperature on the state of erythrocytes, which survived after the combined action of posthypertonic shock (PHS) and amphiphilic compounds, is studied. The effective concentrations (high) and concentrations corresponding to the beginning of the plateau (low) are determined from the dependences of posthypertonic hemolysis of erythrocytes on the concentration of amphiphilic compound (0 ºC). It is found that, when using anionic sodium decyl sulfate in both concentrations, the cells that survived after the action of PHS and amphiphilic compounds are resistant to the temperature rise (from 10 to 37 ºC). When using cationic trifluoroperazine and nonionic decyl-ß,D-glucopyranoside in high concentrations, the erythrocytes have been shown to be sensitive to heat, and in low ones — resistant. Therefore, for all tested substances, the selection from the plateau of such a concentration at which the cells will maintain their integrity when heated is possible.